Advances in the role and mechanism of fibroblasts in fracture healing - Wang, Hui; Qi, Li-li; Shema, Clement; Jiang, Kui-ying; Ren, Ping; Wang, He; Wang, Lei (Frontiers in Endocrinology, 2024)
With the development of social population ageing, bone fracture has become a global public health problem due to its high morbidity, disability and mortality, bone fracture has become a major medical problem that severely impairs the life quality of patients and the life expectancy of the elderly. Fracture healing is a complex phenomenon involving the coordinated participation of immigration, differentiation and proliferation of inflammatory cells, angioblasts, fibroblasts, chondroblasts and osteoblasts which synthesize and release bioactive substances of extracellular matrix components, Mortality caused by age-related bone fractures or osteoporosis is steadily increasing worldwide as the population ages. Fibroblasts play an important role in the process of fracture healing. However, it is not clear how the growth factors and extracellular matrix stiffness of the bone-regeneration microenvironment affects the function of osteoblasts and fibroblasts in healing process. Therefore, this article focuses on the role of fibroblasts in the process of fracture healing and mechanisms of research progress.